Recent developments of Co3O4-based materials as catalysts for the oxygen evolution reaction. Issue 2 (16th December 2021) - Hu, Zhenyu; Hao, Liping; Quan, Fan; Guo, Rui
Abstract : The demand for the development of clean and efficient energy is becoming increasingly pressing due to depleting fossil fuels and environmental concerns. Abstract : The demand for the development of clean and efficient energy is becoming increasingly pressing due to depleting fossil fuels and environmental concerns. Hydrogen is a high energy density source with sanitary combustion products. However, the oxygen evolution reaction (OER) becomes a critical process in the water decomposition reaction due to the slow kinetics of OER limiting electrochemical water splitting. In recent years, among many electrocatalysts, transition metal oxides have received extensive attention due to being inexpensive and showing remarkable activity and stability. Among them, Co3 O4 -based materials have become some of the best candidates for electrocatalysts dedicated to the oxidation of water to oxygen due to their excellent catalytic performance. The recent progress of Co3 O4 -based materials in the OER is summarized in detail, involving pure Co3 O4, doped Co3 O4 and Co3 O4 -based compound composites. Moreover, this review discusses the influence of strategies on the performance of electrocatalysts, such as morphological engineering, interface engineering, synthesis method and doping. At the end of this review, the obstacles, and feasible opinions of Co3 O4 -based materials in OER are put forward, and their future research prospects are also discussed. This review can provide a valuable reference for the research and exploitation of related transition metal oxide catalysts.